SCAR (Sequence Characterized Amplified Region) Analysis for Blast Resistant Evaluation on 12 Genotypes of Rice - , Sobir; Harmi Andrianyta; Mukelar Amir (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2003)
Resistance evaluation to blast disease (Pyricularia grisea) on 12 paddy genotypes was carried out in the green house by using spray inoculated method with race 033 and 041 of P. grisea , and SCAR (Sequence Characterized Amplified Region) marker by using Pib primer pairs. The results revealed that among 12 paddy genotypes were classified into six resistance groups. The first group comprised two genotypes (Jatiluhur and Asahan) having three resistance genes. The second group comprised two genotypes (Oryza malampuzhaensis and O. punctata) having two resistance genes against race 033 and 041. The third group had one resistance gene against race 033, comprised one genotype (Way Rarem). The fourth group comprised one genotype (Danau Tempe) having two resistance genes against 041 race and Pib. The fifth group comprised three genotypes (Kalimutu, Maninjau and Laut Tawar) having two resistance genes against race 033 and Pib. The sixth group comprised two genotypes (Kencana Bali and Cirata) having no resistance gene to blast race 033 and 041, and Pib.  These results indicated that Pib gene did not confer resistance to race 033 and 041 of Pyricularia grisea.  Resistance to race 033 and 041 might be controlled by different resistant gene.   Key words : SCAR, Blast resistant, Rice